2013
DOI: 10.1080/00222933.2012.743614
|View full text |Cite
|
Sign up to set email alerts
|

Age, body size and growth pattern ofArgenteohyla siemersi pederseni(Anura: Hylidae) in northeastern Argentina

Abstract: This article may be used for research, teaching, and private study purposes. Any substantial or systematic reproduction, redistribution, reselling, loan, sub-licensing, systematic supply, or distribution in any form to anyone is expressly forbidden.The publisher does not give any warranty express or implied or make any representation that the contents will be complete or accurate or up to date. The accuracy of any instructions, formulae, and drug doses should be independently verified with primary sources. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Several studies have shown that altitudinal comparisons in age structure and body size of both amphibians and reptiles are especially useful for comparative ecology (Esteban et al, 2004;Chen et al, 2011;Gül et al, 2011;Lou et al, 2012;Özdemir et al, 2012;Cajade et al, 2013;Huang et al, 2013 for amphibians;Roitberg andSimirina, 2006a, 2006b;Guarino et al, 2010;Tomasevic et al, 2010;Arakelyan et al, 2013;Gül et al, 2014 for lizards).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that altitudinal comparisons in age structure and body size of both amphibians and reptiles are especially useful for comparative ecology (Esteban et al, 2004;Chen et al, 2011;Gül et al, 2011;Lou et al, 2012;Özdemir et al, 2012;Cajade et al, 2013;Huang et al, 2013 for amphibians;Roitberg andSimirina, 2006a, 2006b;Guarino et al, 2010;Tomasevic et al, 2010;Arakelyan et al, 2013;Gül et al, 2014 for lizards).…”
Section: Introductionmentioning
confidence: 99%
“…The bright colours (coral‐reddish) are revealed when the frog jumps or swims, and are especially obvious in males calling from the water surface (Cajade et al ., ; cf. plates in Cajade et al ., ). When the frog takes refuge (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Field observations were carried during fieldwork related to other studies (Cajade et al, 2010(Cajade et al, , 2013. The colour patterns were associated with several behavioural display contexts and classified according to Toledo & Haddad (2009).…”
Section: Behavioural Observationsmentioning
confidence: 99%
See 2 more Smart Citations